Scavenger receptor - trypsinová peptidáza IrSRP-1 z klíštěte I. ricinus - Singerová, Barbora (Jihočeská univerzita, 2014)
Scavenger receptors are a large family of structurally diverse molecules that have been implicated in a range of biological functions. In this work, a newly identified multi-domain scavenger receptor-serine protease IrSRP-1 from the tick Ixodes ricinus is characterized. IrSRP-1 is related to the serine protease Sp22D from the mosquito Anopheles gambiae. IrSRP-1 is expressed mainly in the tick gut but also in hemocytes, Malpighian tubules, tracheas and ovaries of fully fed females. This was confirmed with Western blots and immunohistological labeling with antibodies raised against recombinantly expressed IrSRP-1 trypsine-like domain. According to acquired qRT-PCR profiles relative expression of IrSRP-1 is strongly up-regulated during female feeding and remains unchanged in ticks experimentally injected with various microbes. Functional characterization by RNA interference revealed that lowering IrSRP1 expression leads to a higher mortality rate during tick female feeding.
Scavenger receptor - trypsine-like protease IrSRP1 from the tick Ixodes ricinus
Keywords: scavenger receptor; serinová proteáza; I. ricinus; scavenger receptor; serine protease; I. ricinus